Marijuana’s Dose-Dependent Effects in Daily Marijuana Smokers - Ramesh, Divya (Exp Clin Psychopharmacol, 2013)
Active marijuana produces significant subjective, psychomotor, and physiological effects relative to inactive marijuana, yet demonstrating that these effects are dose-dependent has proven difficult. This within-subject, double-blind study was designed to develop a smoking procedure to obtain a marijuana dose–response function. In four outpatient laboratory sessions, daily marijuana smokers (N = 17 males, 1 female) smoked six 5-s puffs from 3 marijuana cigarettes (2 puffs/cigarette). The number of puffs from active (≥5.5% Δ(9)-tetrahydrocannabinol/THC) and inactive (0.0% THC) marijuana varied according to condition (0, 2, 4, or 6 active puffs); active puffs were always smoked before inactive puffs. Subjective, physiological, and performance effects were assessed prior to and at set time points after marijuana administration. Active marijuana dose-dependently increased heart rate and decreased marijuana craving, despite evidence (carbon monoxide expiration, weight of marijuana cigarettes post-smoking) that participants inhaled less of each active marijuana cigarette than inactive cigarettes. Subjective ratings of marijuana “strength,” “high,” “liking,” “good effect,” and “take again” were increased by active marijuana compared with inactive marijuana, but these effects were not dose-dependent. Active marijuana also produced modest, non-dose-dependent deficits in attention, psychomotor function, and recall relative to the inactive condition. In summary, although changes in inhalation patterns as a function of marijuana strength likely minimized the difference between dose conditions, dose-dependent differences in marijuana’s cardiovascular effects and ratings of craving were observed, whereas subjective ratings of marijuana effects did not significantly vary as a function of dose.